Self-Organized Fission Control for Flocking System. (2nd February 2015) - Liu, Mingyong; Yang, Panpan; Lei, Xiaokang; Li, Yang
Abstract : This paper studies the self-organized fission control problem for flocking system. Motivated by the fission behavior of biological flocks, information coupling degree (ICD) is firstly designed to represent the interaction intensity between individuals. Then, from the information transfer perspective, a "maximum-ICD" based pairwise interaction rule is proposed to realize the directional information propagation within the flock. Together with the "separation/alignment/cohesion" rules, a self-organized fission control algorithm is established that achieves the spontaneous splitting of flocking system under conflict external stimuli. Finally, numerical simulations are provided to demonstrate the effectiveness of the proposed algorithm.